Regional differences in interhemispheric structural fibers in healthy, term infants. Issue 3 (28th July 2016) - Makki, Malek I.; Hagmann, Cornelia
Abstract : Using fiber tracking we investigated the early interhemispheric to cortical development by segmenting the corpus callosum (CC) in five substructures, genu, rostrum, body, isthmus, and splenium, and to examine gender differences in healthy, term neonates. Twenty neonates (11 boys aged 39 ± 2 days, nine girls aged 39 ± 1 days) were scanned in natural sleep with diffusion tensor imging and 35 gradient directions. Fiber tracking was performed using the FACT algorithm. The CC was segments in five substructures on midsagittal imaging. The fiber axial and radial diffusion were measured along with apparent diffusion coefficient and fractional anisotropy. Volume measures were performed for each of these substructures using high‐resolution isotropic 3D T1‐weighted images. Radial and mean diffusivity in all measured interhemispheric connections were significantly higher in male newborn infants than in female. Second, a gender‐dependent regional difference of the measured interhemispheric connections exists. There was no volume difference between boys and girls in any of the five studied sudsubstructures. In addition there was no association between macrostructural and microstructural differences either in boys or girls. The cytoarchitecture and the integrity of the interhemispheric fibers is more developed in female infants in all subdivisions of the CC, except for the isthmus. This might result from a larger axonal diameter, highly packed fibers, or more well‐developed myelin sheath. © 2016 Wiley Periodicals, Inc. Abstract : (A) Diffusion encoded color map showing the 5 subdivisions of the corpus callosum: the genu (Ge), the rostral‐body (Ro), the body (Bo), the isthmus (Is), and the splenium. (B) Sagittal view of a neonate to demonstrate the fibers that cross the 5 sub‐structures and inter‐connect the 2 hemispheres. On (C) axial view of the resulting fiber pathways crossing the genu, the rostral‐body, and the body. On (D) remaining 2 pathways are seen the isthmus and the splenium. There was a gender dependent regional difference of the measured interhemispheric connections.